What is hidden behind the category «unaccompanied Moroccan minors»: rampant fear, European contradictions and consecuences for Social Work - Jiménez Sedano, Livia; Izquierdo Collado, Juan de Dios (Cuadernos de Trabajo Social, 2013)
Confronted with the presence of children who migrate on their own from Morocco to Spain, policies have become oriented towards repatriation, which poses ethical and theoretical problems. Social intervention with these children is marked in many ways by the category of «unaccompanied Moroccan minors» imposed on them. This label (a) implies a series of contradictions between their status as «minors» and as «foreigners», which places us squarely in the debates in the European Union about what it means to be «European»; (b) justifies repatriation on the basis of long-standing historical fears of Islam and Muslim culture; and (c) has practical and psychological consequences for the lives of boys and girls thus labelled and for the social intervention professionals working with them. We propose a reflection on all of these elements and to do so, utilize the concept of «menización1 of boys and girls»: how do bureaucratic administrations define, classify and manage these migrants and what are the consequences?
Keywords: unaccompanied Moroccan minors; superior interest of the minor; children’s rights; vulnerability of minors.